The promising anxiolytic effect of Passiflora tripartita var. mollissima assessed in animal models: A systematic review - Llanos-Román, María Noemí (2025)
Objectives: To provide an overview of the scientific publications that determined the anxiolytic effect of the Passiflora tripartita var. mollissima plant evaluated in animal models. All this with the expectation of determining how much progress has been made in this line of research and what approaches could be considered to complement the knowledge acquired to take advantage of the potential of this plant. This review focused on recovering the main details and findings of the publications on the anxiolytic effect of P. tripartita var. mollissima to analyze and contrast them. Materials and methods: In this study, searches were carried out using 4 databases: Dimensions, Scopus, Google Scholar and Pubmed, from October 2024 to January 2025. Results: After evaluating that the publications are experimental research works and that they evaluated the anxiolytic effect of Passiflora tripartita var. mollissima in animal models, it was determined that only 8 studies met these inclusion criteria. Conclusions: Since the evaluated investigations had different methodological approaches to evaluate the anxiolytic effect of this plant, this could be a factor in the fact that there are still no conclusive studies on its capacity as an anxiolytic. This review shows that it is still necessary to go beyond the isolation, identification and characterization of the secondary metabolites that are attributed to be responsible for the anxiolytic effect, so research should continue to determine toxicity, mechanisms of action, dose-response of secondary metabolites, pharmacokinetic studies and, based on this, finally reach clinical trials.